Christ the Redeemer: The Jubilee of the Jubilees - Wisa, Botros; Sidrak, Yousry (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
According to the Bible, the year of Jubilee is the seventh year of the seven-year agricultural cycle mandated by the Torah for the land of Israel. It is a time in which the themes of personal liberty, restitution of property, and rest for the land, are dominant. In Luke 4, and quoting Prophet Isaiah, Jesus claimed that he has been sent to proclaim release to the captives, recovery of sight to the blind, and to set free those who are oppressed. This research article adopts a historical and mathematical approach to show the relationship between the meaning and concept of the Jubilee and the redemptive work of Jesus Christ. It shows that Jesus Christ is, indeed, the Jubilee of the Jubilees, or the ultimate Jubilee, who was sent to set free, once for all, those who have been enslaved. Calculations indicate that exactly 50 Jubilees have passed since God’s flood of judgement to God’s final redemption of mankind by the atoning cross of Jesus Christ. Moreover, the article shows that those 50 Jubilees can be further divided into five equal Eras, of exactly ten jubilees each, i.e. 490 years or 70 weeks, a fact that is alluded to in Daniel 9:24.